Changes in number of NK cells after one year from coronary artery bypass graft - Hak, L; Wieckiewicz, J; Mysliwska, J; Szyndler, K; Siebert, J; Rogowski, J (Termedia Publishing House Ltd., 2009)
Natural Killer cells (NK cells) are components of nonspecific immune response involved in the defense against viral and bacterial infections. Basing on the CD56 cell surface antigen density human NK cells may be divided into two distinct subpopulations: CD56dim - "cytotoxic subset" and CD56bright - "regulatory subset". Our previous work revealed that coronary heart disease (CHD) patients are characterized by a reduction in absolute values and percentage of the CD3-CD56dim and CD3-CD56+ cells. CHD is inflammation dependent disease. Therefore we decided to estimate NK cells status in CHD patients after one year from coronary artery bypass graft (CABG). This procedure improves the heart and vascular status in patients and also remove inflammatory burden. Blood was collected from eighty five patients from the Clinic of Cardiosurgery of the Medical University of Gdańsk before CABG. Blood from eleven CHD patients was examined ones more after one year from CABG. Seventy seven people, of similar age, with excluded coronary heart disease were enrolled into the study as a control group. Percentage of the CD3-CD56+, CD3-CD56dim and CD3-CD56bright cells were analyzed in all samples by flow cytometry. Before CABG blood of the CHD patients was characterized by a low percentage of the CD3-CD56+ and CD3-CD56dim subsets in comparison to control group. However when number of cells were analyzed within one year after CABG we observed a rise of the CD3-CD56+ and CD3-CD56dim cells percentage. The increase of cell percentage was relevant when data were compared to control group and to the results obtained from CHD group before CABG. It may be concluded that a lower NK cells number in CHD is a consequence of inflammation and further that this number may be treated as marker of inflammation.